Editorial - I.D. Mothoagae (Acta Theologica)
The articles published in this Acta Theologica Supplementum 36 were put through a rigorous double-blind peer-review process in accordance with the required academic standard set for this journal and that of the Department of Higher Education and Training. The authors in this Supplementum critically engage the topic of the transmission and reception of biblical discourse in Africa from diverse frames of reference, by applying various interpretational lenses. These hermeneutical lenses function as theoretical tools to analyse and grapple with the question of the strategies used by Western missionaries. The reception and transmission of the Bible in Africa was not an innocent enterprise. For this reason, African biblical scholars, particularly those applying their hermeneutical lenses as theoretical tools, and scholars within the social sciences have argued that the Christian corpus of literature that was translated and composed during “Christianisation”, “colonisation”, and “civilisation”, using the strategies of conversion and assimilation of the “wretched”, are by their very nature colonial products.